The Proportion of Meaning and Form; the Accordance of Mosque Architecture and Prayer - Hamed Iman Talab; Somayeh Gerami (هنر اسلامی, 2012)
The purpose of architecture in religious art especially with an Islamic viewpoint is determining the line between material and mind, body and spirit. In the architecture of a mosque, focusing on spiritual and divine matters and converging on geometrical and mathematical creates a philosophical and theoretical outlook that is unique of its kind. In Islamic art, agreement with the spirit of Islam that of monotheism is the most significant decorative architectural aspect of mosque architecture. In the relation between form and meaning there are mutual understandings; this mutual agreement is nothing more than assimilating to the holy morality of God that seeks for divine perpetuity. This eternity is rooted in the essence of the philosophy of God and mankind. In other words, a mosque is place where diverse arts meet and a sacred and divine affiliation is created through the bond between God and mankind.